IL-10-Producing ILCs: Molecular Mechanisms and Disease Relevance - Sun, Hui; Wu, Yuzhang; Zhang, Yi; Ni, Bing (Frontiers in Immunology, 2021)
Innate lymphoid cells (ILCs) are mainly composed of natural killer (NK) cells and helper-like lymphoid cells, which play a vital role in maintaining tissue homeostasis, enhancing adaptive immunity and regulating tissue inflammation. Alteration of the distribution and function of ILCs subgroups are closely related to the pathogenesis of inflammatory diseases and cancers. Interleukin-10 (IL-10) is a highly pleiotropic cytokine, and can be secreted by several cell types, among of which ILCs are recently verified to be a key source of IL-10. So far, the stable production of IL-10 can only be observed in certain NK subsets and ILC2s. Though the regulatory mechanisms for ILCs to produce IL-10 are pivotal for understanding ILCs and potential intervenes of diseases, which however is largely unknown yet. The published studies show that ILCs do not share exactly the same mechanisms for IL-10 production with helper T cells. In this review, the molecular mechanisms regulating IL-10 production in NK cells and ILC2s are discussed in details for the first time, and the role of IL-10-producing ILCs in diseases such as infections, allergies, and cancers are summarized.